The famous speeches of the eight Chicago anarchists in court. When asked if they had anything to say why sentence of death should not be passed upon them. October 7, 8 and 9, 1886. [Speeches of A. Spies, M. Schwab a.o. With pref. by L.E. Parsons] (Parsons, 1910)
With: Twenty-fifth anniversary, eleventh of November. Memorial edition.